Pengaruh Bahan Ajar Elektronik Interaktif Bermuatan Karakter dengan Pendekatan Saintifik pada Materi Usaha dan Energi Terhadap Pencapaian Kompetensi Siswa Kelas X SMA - Muhammad Ikmal; Yenni Darvina; Murtiani Murtiani (PILLAR OF PHYSICS EDUCATION, 2018)
The achievment of Students Competence still becomes a problem that is caused by several factors. Therefore this research is conducted to give solution. The solution is using interactive electronic teaching material based character value with scientific approach that aims to improve student holistic competence in tenth garde of SMA N 13 Padang. The type of this research is quasi experiment research with randomized control group only design. The sample of this research is taken using cluster random sampling technique. The data analysis techniques are adescription in graphic form for character competences, equality test of two averages for skill and knowledge competences. The result of this research shows that the average value study result competences and observation of experiment class is higher than control class in all sectors. The data analysis result of sample class is normaly distributed and homogenous thus it is used t-test with ttable = 2,00. The averages of skill competences in experiment class is 78,03 and control class is 72,88 statisticaly tcount=4,93, the averages of knowledge competences in experiment class is 76,84 and control class is 66,72 statisticaly tcount = 7,21, the averages of skill competences in experiment class 69,54 and control class is 61,03 statisticaly tcount =3,52. From t-test, it can be seen that tcount < ttable so that Ho is rejected and Hi is accepted, it can be concluded that there is an significant impact on the using of interactive electronic teaching material based character  with scientific approach  on work and energy  to the achievement holistic competence of student is 0,05.